2021
DOI: 10.1002/cbdv.202000917
|View full text |Cite
|
Sign up to set email alerts
|

Response to Salinity in Legume Species: An Insight on the Effects of Salt Stress during Seed Germination and Seedling Growth

Abstract: The process of soil salinization and the preponderance of saline water sources all over the world represent one of the most harmful abiotic stress to plant growth. This pointed to the importance of obtaining plants which are tolerant or resistant to salt, considering that projection of climate change for the coming years indicate an increase in temperature and rain scarcity. In the current study, the effect of NaCl was investigated on germinating seeds of Lathyrus sativus L., Vicia sativa L., Vigna radiata L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…A possible reason for these results is that high salinity played a role in inhibiting microbial activity ( Whittle et al, 2022 ) under moist conditions to maintain higher seed viability. In addition, it was possible that salt stress triggered an increase in the phenolic compounds and flavonoids level ( Tlahig et al, 2021 ) to protect seeds from microorganisms, and this stress may contribute to antioxidant defense under conditions similar to those in the aging experiment as mentioned above. This conclusion was supported by the interaction between groundwater level and salinity.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for these results is that high salinity played a role in inhibiting microbial activity ( Whittle et al, 2022 ) under moist conditions to maintain higher seed viability. In addition, it was possible that salt stress triggered an increase in the phenolic compounds and flavonoids level ( Tlahig et al, 2021 ) to protect seeds from microorganisms, and this stress may contribute to antioxidant defense under conditions similar to those in the aging experiment as mentioned above. This conclusion was supported by the interaction between groundwater level and salinity.…”
Section: Discussionmentioning
confidence: 99%
“…Salinity tolerance and response mechanisms differ according to many parameters such as salt exposure time, salt concentration, plant genotypes and environmental factors. In some plant species and varieties, stress factors cause a lot of damage, while in others, the level of this damage is less (Babalik & Göktürk Baydar, 2021;Tlahig et al, 2021;Tokarz et al, 2021). Since most crops are sensitive to salinity, an increase in salt content causes yield loss.…”
Section: Introductionmentioning
confidence: 99%
“…However, abiotic stress (e.g., drought, salt, and cold) can affect the flavonoid biosynthetic pathway by regulating flavonoid transport and the expression and accumulation of related proteins, finally affecting the flavonoid content in plants ( 17 ). Previous studies have shown that salt stress significantly inhibits the germination of legume crops (including Lathyrus sativus, Vicia sativa, Vigna radiata , and Vigna unguiculata ) but increases the flavonoid content in their seeds ( 18 ). Besides, another study reported significant differences in the flavonoid content and anti-inflammatory effects of soybean when seeds were germinated under different abiotic stress treatments ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that abiotic stress could increase the content of total phenolic compounds and total flavonoids in soybean ( Glycine max ) and mung bean ( V. radiata ) sprouts ( 19 , 20 ). Therefore, the regulation of flavonoid biosynthesis is considered an important regulatory mechanism of legume crops in response to salt stress ( 18 ). In another study, Gu et al ( 21 ) demonstrated that moderate drought stress treatment could increase flavonoid content in plants.…”
Section: Introductionmentioning
confidence: 99%